(untitled) (IITM Journal of Business Studies, 2025)
In the realm of investment, Environmental, Social, and Governance (ESG) criteria have gained prominence as critical factors influencing investment decisions. ESG focused funds invest in companies that demonstrate strong practices in environmental sustainability, social responsibility, and sound governance. Conversely, Anti-ESG funds may invest in companies that do not prioritize or align with these principles. The research process here involves a Literature Review and Data Collection on ESG investing and Anti ESG strategies, followed by the Selection of Investment Portfolios for a well-rounded analysis. Secondly, there is a Performance Analysis of the portfolios, Risk Assessment, and Stakeholder opinion. Further, Statistical Analysis and Sensitivity Analysis are used to draw meaningful Conclusions and Recommendations for investors.